2018
DOI: 10.15625/0866-7136/12294
|View full text |Cite
|
Sign up to set email alerts
|

Comparative stable walking gait optimization for small-sized biped robot using meta-heuristic optimization algorithms

Abstract: This paper proposes a new way to optimize the biped walking gait design for biped robots that permits stable and robust stepping with pre-set foot lifting magnitude. The new meta-heuristic CFO-Central Force Optimization algorithm is initiatively applied to optimize the biped gait parameters as to ensure to keep biped robot walking robustly and steadily. The efficiency of the proposed method is compared with the GA-Genetic Algorithm, PSO-Particle Swarm Optimization and Modified Differential Evolution algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…4. Hence three selected curves P 1 , P 5 , P 10 can be considered as ideal sinus shape, and then completely shown as follows, (developed from [18]).…”
Section: Proposed Wpg Generatormentioning
confidence: 99%
See 2 more Smart Citations
“…4. Hence three selected curves P 1 , P 5 , P 10 can be considered as ideal sinus shape, and then completely shown as follows, (developed from [18]).…”
Section: Proposed Wpg Generatormentioning
confidence: 99%
“…The 10 joint-angular curves located at two humanoid legs in 1-step stepping duration show possible to be expressed using only P 1 = [P 1x , P 1y , P 1z ], P 5 = [P 5x , P 5y , P 5z ] and P 10 = [P 10x , P 10y , P 10z ] based on the inverse trigonometric humanoid equations. Then the pseudo-kinetic technique exploiting humanoid joint-rotating values is used, and shown at (4), in which x l , y l , z l , x r , y r , z r , l l , l r , θ A , θ B , θ C , θ D represent kinetic parameters of humanoid (consulted more in [18]).…”
Section: Proposed Wpg Generatormentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is unnecessary to present in this work. Many former investigators have indicated that the MOPSO is a prominent solution to achieve a reliable global point [17,22,23]. The implementations of the RBF models and the MOPSO are performed using the Isight 5.8 software.…”
Section: Instructions For Authorsmentioning
confidence: 99%